Multi-level and lineage-specific interactomes of the Hox transcription factor Ubx contribute to its functional specificity - Carnesecchi, Julie; Sigismondo, Gianluca; Domsch, Katrin; Baader, Clara Eva Paula; Rafiee, Mahmoud-Reza; Krijgsveld, Jeroen; Lohmann, Ingrid (Nature Communications, 2020)
Transcription factors (TFs) control cell fates by precisely orchestrating gene expression. However, how individual TFs promote transcriptional diversity remains unclear. Here, we use the Hox TF Ultrabithorax (Ubx) as a model to explore how a single TF specifies multiple cell types. Using proximity-dependent Biotin IDentification in Drosophila, we identify Ubx interactomes in three embryonic tissues. We find that Ubx interacts with largely non-overlapping sets of proteins with few having tissue-specific RNA expression. Instead most interactors are active in many cell types, controlling gene expression from chromatin regulation to the initiation of translation. Genetic interaction assays in vivo confirm that they act strictly lineage- and process-specific. Thus, functional specificity of Ubx seems to play out at several regulatory levels and to result from the controlled restriction of the interaction potential by the cellular environment. Thereby, it challenges long-standing assumptions such as differential RNA expression as determinant for protein complexes.
Gesehen am 08.10.2020